Peculiarities of Involving a Specialist in the Preparation and Conduct of Interrogation at the Stage of Pre-Trial Investigation - O. V. Rodiuk (Bulletin of Kharkiv National University of Internal Affairs)
The article provides a comprehensive analysis of the legal and practical framework for involving specialists in interrogation at the pre-trial investigation stage. It is noted that in the current conditions of crime investigation, the requirements for the quality of information collected and the objectivity of evidence are increasing. This necessitates the involvement of specialists from various fields of knowledge – criminologists, psychologists, doctors, linguists, teachers and others – with a view to improving the effectiveness of investigative actions. Specialists not only provide technical and methodological support for interrogation, but also contribute to a deeper understanding of the individual characteristics of the person being interrogated, which allows for adaptation of communication tactics and minimisation of the risks of obtaining distorted information.